KESEHATAN MENTAL MATERNAL: APAKAH BERHUBUNGAN DENGAN TUMBUH KEMBANG ANAK USIA 0-36 BULAN? - Nurulicha Nurulicha; Perwitasari Perwitasari (JURNAL KESEHATAN INDRA HUSADA, 2022)
Introduction: children are superior assets for a nation as their productive roles are expected to bring the supreme hope for the future generation. Because their growth and development are critical during golden age period (0-5 years) so that evitable risk factors should be identified to prevent delays in both aspects. This study aimed at examining the analytical correlation between maternal mental health and children growth and development age 0-36 months. Methods: quantitative method with cross-sectional approach were used. A total of 24 mothers and their children at Posyandu Melati Bogor were recruited using purposive sampling technique. Instruments of KPSP, Z-score indexes, and PHQ-9 were used to measure the variables. Results: the prevalence of maternal mental health disorders were 41.7%, children with growth (BB/TB and TB/U) and development delays were about 33.3% and 41.7%, respectively. There was a significant correlation between maternal mental health and children growth (TB/U) (p-value 0.0032) with Odds Ratio (OR) 9 (95% CI: 1.26 – 63.89). Conclusions: a mother with mental health disorder symptoms are 9 times more likely to have children with growth delayed in TB/U (stunting) than a mother with no symptoms of mental health disorders. Keywords: maternal mental health, growth, development